Imaging Platelet Processes and Function—Current and Emerging Approaches for Imaging in vitro and in vivo - Montague, Samantha J.; Lim, Yean J.; Lee, Woei M.; Gardiner, Elizabeth E. (Frontiers in Immunology, 2020)
Platelets are small anucleate cells that are essential for many biological processes including haemostasis, thrombosis, inflammation, tumour metastasis and wound healing. These minute disk shaped fragments are produced from megakaryocytes and contain many granules that hold growth factors, chemokines and other platelet-activating molecules and proteins. Platelets also have an open canalicular system (OCS), important for protein transport, and a plethora of membrane surface receptors that are vital for platelet activation and thus function, and for interactions with other cells. Platelets circulate in blood and in order to perform all of their roles in biology, platelets must be able to arrest their movement at an appropriate site and time. Our knowledge of how platelets achieve this has expanded as our ability to visualise and quantify discreet platelet events has improved. Platelets are exquisitely sensitive to changes in blood flow parameters and so the visualisation of intricate platelet processes provides a substantial challenge to the platelet imaging field. Applications of modern imaging systems to study platelet function has led to major advancements in our understanding of molecular events mediating platelet adhesion from a single-cell perspective, through to platelet recruitment and activation, leading to thrombus (clot) formation. This review will discuss current platelet imaging techniques in vitro and in vivo, describing how the advancements in imaging have helped answer/expand on some key biological questions regarding platelet aggregation and thrombus formation, how platelet imaging has enhanced our understanding of key events in thrombus formation, highlighting current knowledge that has been advanced as researchers have applied both in vitro and in vivo imaging techniques. We will review the limitations of current imaging techniques, and questions in thrombosis research that remain to be addressed.